Peer-to-Peer Lending: Growth, Trends, and Economic Impact Analysis - Ikhlash, Muhammad; Sembiring, Tiara Ayodhya Maharani (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Purpose – This study aims to analyze the growth trends and economic impact of peer-to-peer (P2P) lending, highlighting its role in financial inclusion and support for small businesses, particularly in contexts with limited access to traditional banking services. Design/methodology/approach – The research employs a bibliometric analysis method to evaluate scientific publications on P2P lending from 2007 to 2024, utilizing data from the Scopus database. The study uses Biblioshiny WebInterface software connected via R-Packages to map research trends, author productivity, and international collaborations. Findings – The analysis reveals a significant increase in P2P lending research publications, peaking in 2021. Key authors, institutions, and countries contributing to the field are identified, with China and the USA leading in research output and collaboration. The study highlights the dual focus on economic and technological aspects of P2P lending in the literature. Research limitations/implications – The research is limited to articles, conference papers, and conference reviews, excluding other document types such as editorials and errata. This exclusion may restrict a comprehensive understanding of the entire spectrum of literature on P2P lending. Practical implications – The findings underscore the importance of P2P lending in enhancing financial inclusion and providing alternative financing for SMEs. The identified research trends and influential contributors offer valuable insights for policymakers and practitioners to support the growth and regulation of P2P lending platforms. Originality/value – This study provides a comprehensive bibliometric analysis of P2P lending research, offering a detailed overview of publication trends, key contributors, and international collaboration networks. It contributes to the existing literature by mapping the development and focus areas of P2P lending research, serving as a reference for future studies and policy formulation.